The Impact of the COVID-19 Pandemic on Green Societies 2021
DOI: 10.1007/978-3-030-66490-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Attainment of Solar E-waste Recycling Concerning to COVID-19 Crisis: A Review

Abstract: Solar energy is looked at as a critical component to fight against increased climate change. It is seen as the green solution for the increased demand in energy, but the problems that will occur after 20-30 years when these solar panels have to be disposed of are seldom considered. Due to increased growth in the development and utilization of solar energy resources, the disposal of waste solar panels has become problematic. Photovoltaic systems are in the lead because they are cost-effective, and it has increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…According to Nieto et al, 5 in the United States of America, different states classify solar waste differently, some categorize them as normal solid waste to be managed through landfills while other States have classified them as hazardous waste materials like in the case of European Union that calls for specialized approach in their management. In broad‐spectrum solar waste falls under the electronic waste categories, but recent studies have shown that they are hazardous waste materials 6 …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Nieto et al, 5 in the United States of America, different states classify solar waste differently, some categorize them as normal solid waste to be managed through landfills while other States have classified them as hazardous waste materials like in the case of European Union that calls for specialized approach in their management. In broad‐spectrum solar waste falls under the electronic waste categories, but recent studies have shown that they are hazardous waste materials 6 …”
Section: Literature Reviewmentioning
confidence: 99%
“…In broad-spectrum solar waste falls under the electronic waste categories, but recent studies have shown that they are hazardous waste materials. 6 Ockwell et al 7 observes that, the world generated 53.6 metric tons of electronic waste in the year 2019 and this is projected to grow by 40% by the year 2030. About 80% of general electronic waste globally in developing countries is handled informally.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation